Practical Approach to Transcatheter Aortic Valve Implantation and Bioprosthetic Valve Fracture in a Failed Bioprosthetic Surgical Valve - Maarten Vanhaverbeke; Ole De Backer; Christophe Dubois (Journal of Interventional Cardiology)
Bioprosthetic surgical aortic valve failure requiring reintervention is a frequent clinical problem with event rates up to 20% at 10 years after surgery. Transcatheter aortic valve-in-valve implantation (ViV-TAVI) has become a valuable treatment option for these patients, although it requires careful procedural planning. We here describe and illustrate a stepwise approach to plan and perform ViV-TAVI and discuss preprocedural computerized tomography planning, transcatheter heart valve selection, and implantation techniques. Particular attention is paid to coronary artery protection and the possible need for bioprosthetic valve fracture since patients with small surgical aortic bioprostheses are at a risk of high residual gradients after ViV-TAVI. Considering updated clinical data on long-term outcomes following ViV-TAVI, this approach may become the default treatment strategy for patients with a failing surgical aortic bioprosthesis.